The Effect of Knowledge Sharing on the Service Innovation Performance:An Empirical Study on Restaurant in North Kalimantan, Indonesia - Hidayat, Nurul; Lee, Cheng-Wen (Metris: Jurnal Sains dan Teknologi, 2018)
This research was conducted on restaurant business in North Kalimantan Province, Indonesia. To improve the performance of service innovation, companies need knowledge gained from knowledge sharing activities. A number of 150 employees working in the restaurant businesses in North Kalimantan participated in this study. The data were collected using survey method with questionnaire. The survey responses submitted by respondents in this study indicated that the influence of knowledge sharing on the performance of service innovation showed significant results. Knowledge sharing activities in this study have a positive effect on innovation performance of restaurant business services in North Kalimantan.